DOWNWARD VERTICAL COMMUNICATION IN IMPROVING SERVICE QUALITY AT WISMA BHIMA CAKTI KOPO - Ivan Maulana Yusuf; Augustini Augustini; Ruhimat Ruhimat (Gema Kampus IISIP YAPIS Biak, 2025)
AbstractThis study aims to analyze the vertical communication between leaders and employees and its impact on the quality of service at Wisma Bhima Cakti Kopo. A qualitative approach is used through in-depth interviews with key informants and supporters. Based on the theory of vertical communication, the results of the study show that downward communication has a more significant influence on employee readiness in carrying out tasks, through work instructions, task explanations, regulatory notices, and work motivation. Meanwhile, upward communication functions as a feedback tool, although its effectiveness is still limited. These two types of communication complement each other and affect service quality indicators, such as reliability, competence, accessibility, communication, and security. To improve the quality of service, improvements are needed in the delivery of more structured downward communication and more responsive and transparent upward communication. The combination of the two can create a productive work environment and increase guest satisfaction.